Rethinking optimum currency area theory: endogenous synchronisation of shocks in Europe - Garcia, José Pedro (2017)
This work aims to assess whether the hypothesis of endogenous synchronisation of shocks is verified in the European Economic and Monetary Union (EMU). A state-space model, which yields time-varying coefficients, is estimated with structural demand and supply shocks to several European economies and those of Germany, which serves as a benchmark country. The goal is to understand to what extent have structural shocks to the German economy become more or less correlated with shocks to the other European economies throughout the EMU experience. The study is also applied to U.S. regions in order to have a useful standard of comparison. Even though the hypothesis of endogeneity cannot be unequivocally corroborated in Europe, I show that there is a large set of EMU member states whose demand shocks are becoming increasingly desynchronised with those of Germany. This may cast doubt on the prospects of a successful European monetary union as it is today. Moreover, amongst the key findings there is also proof that U.S. regions are a much more cohesive economic bloc than European countries.